Cloud-based routing resource allocation in cognitive radio network - M. N., Morshed; Sabira, Khatun; Fakir, Md Moslemuddin; M. Z., Ibrahim; Saifudin, Razali; Yugeraj, Ramajayam (Universiti Teknikal Malaysia Melaka (UTeM), 2018)
Wi-Fi Direct technology is enabled to support multiple services to be done via Wi-Fi connection. It provides the most efficient method to develop ad-hoc community among mobile devices for connecting quickly with one another without needing an access to network. It allows to communicate at common Wi-Fi rates for various applications including document exchange and online connection. This one-Stop WiFi Direct application is able to connect a device to a single device at a time, i.e., only peer to peer communication is allowed within one hop. Hence, multi-device communication within multi-hop distance in a trusty Cognitive Radio (CR) network environment is in demand. This paper presents the development of an Android based application with optimum cloud routing service to transfer files or chatting via Wi-Fi Direct technology in CR network. A system is developed using smart phones (with developed applications) and nodes with WI-FI connection. An indirect multi-hop routing approach is created if more devices transfer files simultaneously from hop to hop. After login and initializing, a device discovers the neighboring nodes first and then connects those (as necessary) to transfer file or start chatting. The very moment a connection is established, a log file is generated in internal memory and save a backup copy in cloud containing necessary networking information of the client devices. The aim of these backup log files is for forensic investigation for intrusion detection/prevention and secured communications. Then the chatting or file transfer is carried out between the connected devices either in single or multi-hop routes. Results show that the system’s efficiency is around 92%. It shows that multi-device, multi-hop Wi-Fi Direct services can be implemented using Android devices with Eclipse Java programming in CR networks.